Acute effects of carbohydrate gel and isotonic usage on power, heart rate and glucose levels in elite cyclists - Suna, Gürhan; Türkay, İbrahim Kubilay (Progress in Nutrition, 2020)
Study Objective: This study aimed to compare the acute effects of carbohydrate gel and isotonic usage on power, heart rate (HR), and glucose levels of elite cyclists. Method: Twenty licensed cyclists participated in the study voluntarily. Cyclists are randomly divided into two groups (The first group: carbohydrate gel receiving group; second group: isotonic drink receiving group). Cyclists performed about one hour of velodrome training. The first group continued to operate using one energy carbohydrate gel in the fifth minute of the training. The second group used a 2 scale (27 g) electrolyte and carbohydrate mixture in 500 ml water and added powder product during the training. Athletes’ mean HR values were recorded with the Garmin brand watch. The mean power (watt) values of the athletes were also obtained with the Garmin Power meter. Heart rate and power values were compared as the mean values after the training that the athletes applied after carbohydrate gel and isotonic drink intake. OKmeter Optima OK-10H (Taiwan) sugar meter was used in the measurement of blood glucose values of cyclists. Glucose measurement was taken pre- and post-test. The analysis of data was made in the statistical package program by using “Descriptive statistics”, “Independent samples-t Test” and “Repeated Measures Analysis of Variance (ANOVA)” for comparison. Results: There were no significant differences in the mean HR, mean power, and glucose pre-and post-test values of the cyclists who took carbohydrate gel and isotonic drink before and after the training (p >0.05). Conclusion: As a result, carbohydrate gel or isotonic usage during cyclists’ sports activity didn’t effect on performance and physiological properties. Key Words: